2015
DOI: 10.1037/xge0000048
|View full text |Cite
|
Sign up to set email alerts
|

Anxious and egocentric: How specific emotions influence perspective taking.

Abstract: People frequently feel anxious. Although prior research has extensively studied how feeling anxious shapes intrapsychic aspects of cognition, much less is known about how anxiety affects interpersonal aspects of cognition. Here, we examine the influence of incidental experiences of anxiety on perceptual and conceptual forms of perspective taking. Compared with participants experiencing other negative, high-arousal emotions (i.e., anger or disgust) or neutral feelings, anxious participants displayed greater ego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 110 publications
6
108
2
8
Order By: Relevance
“…As a discrete emotion, anxiety is characterized by high arousal, negative valence, a sense of uncertainty, and a low sense of control, and is theoretically distinct from other emotions such as sadness and grief, which are characterized by low arousal (Gray, 1991;Raghunathan & Pham, 1999;Smith & Ellsworth, 1985). Anxiety drains working memory and impairs information processing: anxious individuals utilize working memory on processes such as worrying and ruminating instead of focusing on the task at hand (Eysenck, 1992), and feelings of anxiety increase egocentrism and impair the ability to take another person's perspective (Todd, Forstmann, Burgmer, Brooks, & Galinsky, 2015).…”
Section: Rituals Reduce Anxietymentioning
confidence: 99%
“…As a discrete emotion, anxiety is characterized by high arousal, negative valence, a sense of uncertainty, and a low sense of control, and is theoretically distinct from other emotions such as sadness and grief, which are characterized by low arousal (Gray, 1991;Raghunathan & Pham, 1999;Smith & Ellsworth, 1985). Anxiety drains working memory and impairs information processing: anxious individuals utilize working memory on processes such as worrying and ruminating instead of focusing on the task at hand (Eysenck, 1992), and feelings of anxiety increase egocentrism and impair the ability to take another person's perspective (Todd, Forstmann, Burgmer, Brooks, & Galinsky, 2015).…”
Section: Rituals Reduce Anxietymentioning
confidence: 99%
“…Future research should also test for other social influences that might shape the parameter estimates as dependent variables; for instance, Intentional and/or Unintentional Empathy might increase for people high in anxiety (Todd et al, 2015) or decrease for people high in anticipated emotional exhaustion (Cameron et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent evolutionary survival response is adaptive in some circumstances because it leads to a narrowing of focus, evidenced by improvements in selective attention [96]. In 2015, Todd and colleagues further elucidated this process, by demonstrating that feelings of stress also heighten 'self-focussed attention' ( [106], p. 375) which, in turn, undermines perspective taking. Converging research subsequently revealed that this acquired egocentrism is associated with a reduction in empathy for others [73].…”
Section: Stress: the Precursor To Withdrawalmentioning
confidence: 99%
“…This is known as the 'ultimate attribution error' [89]. To return to a point discussed at the start of the case study, and as highlighted by the doctor within the Schwartz Round, this may be underpinned by the stress-induced selfdirected focus [106]. Another way of viewing this is that stress contributes to decrements in mentalization; 'the capacity to envision mental states in self and others' ( [38], p. 23).…”
Section: Stress As a Precursor For The Depersonalization Of Colleagues?mentioning
confidence: 99%